The Sunni Ideology in “Al-Qur'an dan Terjemahannya” by the Ministry of Religious Affairs - Rodin, Dede (SUHUF, 2023)
This study aims to show how Sunni ideology influences the official Indonesian translation of the Qur'an and explore the reasons behind choosing this particular translation ideology. The primary data consist of a sample of several translations of theological verses from the 2019 edition of “Al-Qur'an dan Terjemahannya”. Interviews and relevant secondary data reinforce the primary data. Employing a critical linguistic approach, this article shows that Sunni ideology influences the translation of theological verses, evident in the selection of translated diction and explanations. The inclination towards this ideology is not only due to the majority of the Indonesian muslim society being Sunni but also because Sunnis are perceived as a religious group characterized by moderation (wasatiyyah), a main characteristic of Islamic teachings. In addition, Sunni moderation aligns with the Indonesian state model based on Pancasila, which accommodates pluralism. Thus, this study proves the hypothesis that a Qur'an translation is shaped not only by linguistic processes but also by ideological considerations